Proposal of a simple grading system integrating cosmetic and tonometric aspects of prostaglandin-associated periorbitopathy. Issue 34 (27th August 2021) - Tanito, Masaki; Ishida, Akiko; Ichioka, Sho; Takayanagi, Yuji; Tsutsui, Aika; Manabe, Kaoru; Shirakami, Tomoki; Sugihara, Kazunobu; Matsuo, Masato
Abstract : Abstract: The distribution of prostaglandin-associated periorbitopathy (PAP) graded using the Shimane University PAP Grading System (SU-PAP) among glaucoma/ocular hypertension subjects using a topical FP or EP2 receptor agonist was reported. A 460 consecutive 460 Japanese subjects (211 men, 249 women; mean age ± standard deviation, 69.9 ± 14.5 years) who had used either a FP agonist (0.005% latanoprost, 0.0015% tafluprost, 0.004% travoprost, 0.03% bimatoprost, or fixed combinations of these) or EP2-agonist (0.002% omidenepag isopropyl) for more than 3 months in at least 1 eye were retrospectively enrolled. Age, sex, prostaglandin, intraocular pressure (IOP) measured by Goldmann applanation tonometry (IOPGAT ) and iCare rebound tonometry (IOPRBT ), difference between IOPGAT and IOPRBT (IOPGAT-RBT ), PAP grade, and PAP grading items were compared among groups stratified by PAP grade or prostaglandins. Of the study patients, 114 (25%) had grade 0 (no PAP), 174 (38%) grade 1 (superficial cosmetic PAP), 141 (31%) grade 2 (deep cosmetic PAP), and 31 (7%) grade 3 (tonometric PAP). The IOPGAT was significantly higher in grade 3 (17.5 ± 5.4 mm Hg) than grades 0 (15.0 ± 5.1 mm Hg, P = .032) and 1 (14.5 ± 4.2 mm Hg, P = .008), and the IOPGAT-RBT was significantly higher in grade 3 (5.8 ± 3.2 mm Hg) than the other 3 grades (1.3–1.9 mm Hg, P < .001 for all comparisons); the IOPRBT was equivalent among the 4 grades. The PAP grade was significantly higher associated with travoprost (2.0 ± 0.8) and bimatoprost (2.0 ± 0.7) than latanoprost (1.0 ± 0.8, P < .001 for both comparisons) and tafluprost (1.0 ± 0.7, P < .001 for both comparisons), but significantly lower associated with omidenepag (0.0 ± 0.0, P < .001 for all comparisons) than the other 4 prostaglandins. Multivariate analyses showed older age (standard β = 0.11), travoprost (0.53, referenced by latanoprost) and bimatoprost (0.65) were associated with higher PAP grades, while tafluprost (−0.18) and omidenepag (−0.73) were associated with lower PAP grades. The PAP graded using SU-PAP reflects the degree of overestimation of the IOPGAT and different severities of PAP among the different prostaglandins. SU-PAP, the grade system constructed based on the underlining mechanisms of PAP, is a simple grading system for PAP that is feasible for use in a real-world clinical situation.